Accessing the genetic diversity of natural populations of Acrocomia aculeata (Arecaceae) through microsatellites - Rodrigues Ortega, Julia; Sousa, Ligiany Gravoche; Oliveira, Dario Alves de; Júnior, Afrânio Farias de Melo; Royo, Vanessa de Andrade; Menezes, Elytania Veiga (Revista Unimontes Científica, 2024)
Acrocomia aculeata holds cultural and economic importance as the second-largest producer of oleaginous fruits in arid and semi-arid regions, with potential for exploitation as an agricultural crop. It is a tropical arborescent species distributed throughout tropical and subtropical Americas, with a significant occurrence of natural populations in the Cerrado biome. Its broad distribution across various landscapes is supported by a mixed reproductive system, diverse pollination strategies, and resilience to environmental stressors. Despite its resilience in fragmented habitats, anthropogenic habitat fragmentation generally harms populations, affecting gene flow and genetic diversity. In this context, this study aimed to assess genetic diversity and structure of natural populations of A. aculeata from northern Minas Gerais using microsatellites. The five natural populations were named according to the municipality where they were collected, being them Espinosa, Mirabela, Claro dos Poções, Grão Mogol, and Itacambira. The results revealed that four SSR loci amplified 46 different alleles, totaling 1352 alleles. The loci showed significant deviations from Hardy-Weinberg Equilibrium, with a mean f of 0.288. Among the populations analyzed, ITA was the most genetically diverse, while ESP was the least diverse. As subpopulations, they displayed high genetic structure, with a mean FST of 0.329 and FIT of 0.484. The study suggests the natural populations of Macaw palm in northern Minas Gerais that can be used for germplasm banks, and the ones that requires human intervention to restore genetic diversity.